Hama Dan Penyakit Pada Tanaman Kakao - Valentino Keytimu; Julianus Jeksen; Henderikus Beja (Institut Nalanda, 2023)
This article presents the results of community service activities carried out in Bloro Village, Nita District, Sikka Regency. This activity aims to overcome pests and diseases in cocoa plants in Bloro Village. The solution to overcome these pests and diseases is through counseling, direct practice and assistance to the people of Bloro Village, especially members of the Plea Puli and Metenler farmer groups, as well as teaching them how to control pests and diseases that often occur in cocoa plantations in Bloro Village, namely the Cocoa Fruit Borer (PBK). ), Cocoa Fruit Rot (BBK) and Helopeltis SPP. In dealing with Pests and Diseases in Cocoa Plants, efforts need to be made, namely by carrying out control techniques such as sarongization, destroying ant nests, and spraying using vegetable pesticides, so that the cocoa plants can provide good and increased production results. It is hoped that this activity can have a sustainable positive impact on the people of Bloro Village, especially members of the Plea Puli and Metenler farming groups and become an inspiring example for being able to overcome pests and diseases in cocoa plants.